mRNA-LNP Vaccines Targeting SmpA-PLD and OmpK-Omp22 Induce Protective Immunity Against Acinetobacter baumannii - Cong Liu; Xingyun Wang; Yueling Zheng; Xingyue Gao; Jiahui Jin; Xing Cheng; Yunjiao He; Peng George Wang (Vaccines)
Background: Acinetobacter baumannii (A. baumannii) has emerged as a critical human pathogen, causing high mortality rates among hospitalized patients and frequently triggering nosocomial outbreaks. The increasing prevalence of multidrug-resistant (MDR) A. baumannii poses a pressing threat to public health. To date, no commercially available vaccine against A. baumannii has been developed for clinical use. messenger RNA (mRNA)–lipid nanoparticle (LNP) vaccines have emerged as a promising vaccination strategy. Methods: In this work, we developed two mRNA vaccines targeting SmpA-PLD and the fusion protein of outer membrane proteins OmpK and Omp22. The mRNA was encapsulated in LNP and administered to BALB/c mice. We evaluated humoral and cellular immune responses, bacterial burden, inflammation, and protective efficacy against A. baumannii infection in a sepsis model. Results: These mRNA vaccines triggered robust humoral and cellular immune responses in BALB/c mice, reduced bacterial burden and inflammation in sepsis models, and provided significant protection against A. baumannii infection. Notably, the OmpK-Omp22 vaccine exhibited superior protective efficacy, reducing bacterial loads in various organs and improving survival rates in the sepsis model compared to the SmpA-PLD vaccine. Conclusions: Our findings demonstrate mRNA-LNP vaccine technology as a versatile and promising platform for the development of innovative therapeutics against A. baumannii, with the potential to mitigate acute disease and promote bacterial decolonization. These findings pave the way for the development of urgently needed and effective antibacterial vaccines.